Downregulation of SLC7A7 Triggers an Inflammatory Phenotype in Human Macrophages and Airway Epithelial Cells - Rotoli, Bianca Maria; Barilli, Amelia; Visigalli, Rossana; Ingoglia, Filippo; Milioli, Marco; Di Lascia, Maria; Riccardi, Benedetta; Puccini, Paola; Dall’Asta, Valeria (Frontiers in Immunology, 2018)
Lysinuric protein intolerance (LPI) is a recessively inherited aminoaciduria caused by mutations of SLC7A7, the gene encoding y+LAT1 light chain of system y+L for cationic amino acid transport. The pathogenesis of LPI is still unknown. In this study, we have utilized a gene silencing approach in macrophages and airway epithelial cells to investigate whether complications affecting lung and immune system are directly ascribable to the lack of SLC7A7 or, rather, mediated by an abnormal accumulation of arginine in mutated cells. When SLC7A7/y+LAT1 was silenced in human THP-1 macrophages and A549 airway epithelial cells by means of short interference RNA (siRNA) a significant induction of the expression and release of the inflammatory mediators IL1β and TNFα was observed, no matter the intracellular arginine availability. This effect was mainly regulated at transcriptional level through the activation of NF-kB signalling pathway. Moreover, since respiratory epithelial cells are important source of chemokines in response to pro-inflammatory stimuli, the effect of IL1β has been addressed on SLC7A7 silenced A549 cells. Results obtained indicated that the down-regulation of SLC7A7/y+LAT1 markedly strengthened the stimulatory effect of the cytokine on CCL5/RANTES expression and release without affecting the levels of CXCL8/IL8. Consistently, also the conditioned medium of silenced THP-1 macrophages activated airway epithelial cells in terms of CCL5/RANTES expression due to the presence of elevated amount of proinflammatory cytokines. In conclusion, our results point to a novel thus far unknown function of SLC7A7/y+LAT1, that, under physiological conditions, besides transporting arginine, may act as a brake to restrain inflammation.